Self-consistent quantum effects in the quark meson coupling model - Panda, P. K. [UNESP]; Braghin, F. L. (American Physical Society (APS), 2002)
We derive the equation of state of nuclear matter for the quark-meson coupling model taking into account quantum fluctuations of the [Formula Presented] meson as well as vacuum polarization effects for the nucleons. This model incorporates explicitly quark degrees of freedom with quarks coupled to the scalar and vector mesons. Quantum fluctuations lead to a softer equation of state for nuclear matter giving a lower value of incompressibility than would be reached without quantum effects. The in-medium nucleon and [Formula Presented]-meson masses are also calculated in a self-consistent manner. The spectral function of the [Formula Presented] meson is calculated and the [Formula Presented] mass has the value increased with respect to the purely classical approximation at high densities. © 2002 The American Physical Society.